"Patrzył na wszystko jakby przez wizjer" - fotografia w "Walcu z Baszirem" Ariego Folmana - Agnieszka Powierska (Images)
“He looked at everything as if through an imaginary camera” – Photography in Ari Folman’s Waltz with Bashir